Students’ Interest in Using Semantic Mapping Technique in Learning English Writing Ability - Wahab, Isnaeni; Astri, Zul (Journal of Indonesian Scholars for Social Research, 2022)
This study aims to out the students’ interest to learn English writing through Semantic Mapping Technique. This research is carried out under a descriptive qualitative paradigm at the Junior High School of Kartika XX-I Makassar. The purposive sampling technique is used to select the sample from the population, which consisted of 70 students in three classes. The chosen sample is the students of A class that consisted of 29 students. The data of the students’ interests is collected by using students’ experiences in learning by using semantic mapping. Those are by observation and questionnaires. Data analysis through data reduction, data presentation, and concluding stages. The result shows that the student's interest to learn writing through the Semantic Mapping Technique is categorized as very high. The students feel motivated, excited, and active in joining the class. Keywords: Semantic Mapping, Learning English, Writing Ability